Effects of feeding increased amounts of wet corn gluten feed on dairy cow metabolism and milk production - Titgemeyer, Evan C.; Bradford, Barry J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experiment was conducted to evaluate the effects of feeding increasing dietary amounts of wet corn gluten feed (WCGF). Eight lactating Holstein cows were housed in a tie-stall facility and fed 1 of 4 diets containing 0, 11, 23, or 34% WCGF on a dry matter basis. To maintain similar nutrient concentrations, alfalfa hay, corn silage, corn grain, soybean meal, expeller soybean meal, and mineral supplements varied across diets. Feed intake, milk production, body weight, and body condition score were monitored, and effects of WCGF inclusion rate were assessed. Increasing the level of WCGF in the diet led to increased feed intake, milk production, and body condition. Concentrations of milk components did not differ among treatments; therefore, yield of energy-corrected milk and solids-corrected milk increased as well. In contrast, increasing dietary WCGF decreased efficiency of production and also decreased ruminal pH, possibly because treatments with greater proportions of WCGF had a decreased mean particle size. As expected, the decreased ruminal pH coincided with changes in ruminal volatile fatty acid concentrations. Furthermore, the rate of fiber digestion after 24 hours decreased when more WCGF was incorporated into diets. Results indicate that adding WCGF to dairy rations can increase energy-corrected milk yield, and this increase seems to be driven, at least in part, by an increase in feed intake.
Dairy Research, 2009 is known as Dairy Day, 2009
Keywords: Dairy; Feed intake; Fiber; Milk yield; Wet corn gluten feed